Critical Discourse Analysis of Pembukaan UUD 1945 Base On the Pesantren Tradition - Randi Muchariman; Hendra Gunawan (Epistemik Press, 2021)
The texture text of Pembukaan UUD 1945 is more complete than the text of Pancasila, but there is still less research or discourse on the Pembukaan compared to Pancasila. This article efforted to fill the empty point with Norman Fairclough’s critical discourse analysis method base on the pesantren tradition as the basis of its analysis. The results showed that the pesantren tradition which is the subject of the study did not assign Pembukaan as an important discourse. Even so, the practice in Pesantren has shown that there is conformity and agreement with the Pembukaan except for the concept of Peoples,s Sovereignty if it is interpreted as democracy based on the Western paradigm. This research has shown a model of democratic practice named Maniis which can be followed up in further research. the Maniis model shows that democracy has been accepted in the axiological aspect but is unacceptable in the different epistemological aspects. In practice, there are no negative consequences for democracy, the Maniis model is actually very democratic and shows the characteristics of civil society. This invention is important because it shows direction and trend in the relation betwen religion and politics in Indonesia. especially related to the study of democracy and Islam in Indonesia.